2018
DOI: 10.3390/w10070880
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temporal Resolution of Rainfall on Simulation of Urban Flood Processes

Abstract: Rainfall exhibits substantial variability, and its temporal resolution considerably affects simulation of hydrological processes. This study aims to investigate the effect of the temporal resolution of rainfall (TRR) on urban flood modeling and to explore how high TRR is required. A routing-enhanced detailed urban stormwater (REDUS) model, which has four layers and accounts for complex urban flow paths, was developed and then applied to the campus of Tsinghua University, Beijing, China. For 30 rainfall events … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…The two river outlets (Figure 2b) located at the Hongwanchong and Qianshan River and two typical pipes (Figure 2a) in the study area were selected. The simulation results of the scalar flowrate time series (Figure 6) at the two basin outlets showed that the model had a high stability, and the flow processes of the two outlets were consistent with other similar studies [45,46]. The typical pipe discharge was also evaluated (Figure 7).…”
Section: Model Rationality Verificationsupporting
confidence: 84%
“…The two river outlets (Figure 2b) located at the Hongwanchong and Qianshan River and two typical pipes (Figure 2a) in the study area were selected. The simulation results of the scalar flowrate time series (Figure 6) at the two basin outlets showed that the model had a high stability, and the flow processes of the two outlets were consistent with other similar studies [45,46]. The typical pipe discharge was also evaluated (Figure 7).…”
Section: Model Rationality Verificationsupporting
confidence: 84%
“…To represent the high heterogeneity of urban catchments, a grid-based distributed urban hydrological model named REDUS (routing-enhanced detailed urban stormwater model) was developed (Lyu et al, 2018). Taking advantage of the urban hydrological model (Pan et al, 2011) and the multilevel urban flooding model (Li et al, 2016), REDUS uses a four-layer structure, including surfaces, road networks, pipe networks, and river networks.…”
Section: Model Setupmentioning
confidence: 99%
“…Variations of the rainfall spatiotemporal resolutions can affect the rainfall-runoff response time and water yield in the hydrological model [ 11 ]. Therefore, it is important to simulate the hydrological response with an appropriate spatiotemporal resolution of rainfall [ 12 , 13 ]. A large number of studies have proved that for small urban catchments, urban flood simulation should use the rainfall data on at least 1–15 min time resolution and 100–1000 m spatial resolution [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%